False-Positive Results for Mycobacterium celatum with the AccuProbe Mycobacterium tuberculosis Complex Assay - Somoskövi, Ákos (American Society for Microbiology, 2000)
Mycobacterium celatum type 1 was found to cross-react in the AccuProbe Mycobacterium tuberculosis complex assay. Subsequently, we found a statistically significant increase in the relative light units with lower temperatures, suggesting that it is necessary to perform this AccuProbe assay at between 60 and 61°C. We also recommend the inclusion of M. celatum type 1 as a negative control.